A case study in photosynthetic parameters of perennial plants growing in natural conditions - Agata Dziwulska-Hunek; Beata Myśliwa-Kurdziel; Arkadiusz Matwijczuk; Mariusz Szymanek (BMC Plant Biology)
Abstract The research objective of this study was to determine the physiological condition of selected legume species growing under natural conditions, based on analysis in them: photosynthetic efficiency, chlorophyll fluorescence lifetime and photosynthetic pigment content. Evaluation of these parameters allows early detection of stress factors affecting the physiology of the plants and the determination of their adaptive capacity. The plants selected for the study included: white clover, red clover, alfalfa, and common sainfoin. The presented results revealed that the photosynthetic activity was lower in red clover but higher in common sainfoin. Longer τ1 and τ 2 fluorescence lifetimes of Chl a were measured in red clover and common sainfoin, while shorter lifetimes were recorded for white clover and alfalfa. Shorter lifetimes suggest greater activity of other chlorophyll excitation pathways, including in particular ones related to energy dissipation in the photosynthetic antennae. The content of chlorophyll a, a + b was noticeably higher in the leaves of red clover, and lower in the leaves of common sainfoin. The varied values of photosynthetic parameters measured in the analyzed perennial plants from the same Fabaceae family indicate the ease with which they adapt to environmental conditions. The studied plants are excellent sources of nitrogen and fodder protein, rendering them interesting in the context of sustainable agriculture. Graphical abstract